Piloting Citizen Science Methods to Measure Perceptions of Carbon Footprint and Energy Content of Food - Armstrong, Beth; Bridge, Gemma; Oakden, Libby; Reynolds, Christian; Wang, Changqiong; Panzone, Luca A; Rivera, Ximena Schmidt; Kause, Astrid; Ffoulkes, Charles; Krawczyk, Coleman; Miller, Grant; Serjeant, Stephen (Frontiers in Sustainable Food Systems, 2020)
There is a food knowledge disconnect between the food research community, and the general population. Food experts know detailed information about foods, but there is a lack of understanding about what citizens know. Citizen science has been used successfully in various fields however, is virtually absent from food research. This pilot study explores the efficacy of Zooniverse citizen science platform as a method of food citizen research, and assesses the impact of response method, food type, portion size and weight information, on estimates of carbon footprint and energy content. Estimates of the carbon footprint (grams of carbon dioxide equivalent) and energy content (Kcal) of ten foods were measured in a 3 (Between: Response Method; multiple-choice, slider, text box) x 3 (Within: portion size; small, medium, large) x 2 (Between: weight information; present, absent) observational survey. Citizens (N=~516, unique IP addresses) were recruited via informal email networks. Kruskal-Wallis and Chi-square analyses compared citizen estimations with validated values, and assessed the impact of the variables on estimations. The majority of carbon footprint and energy content estimates were inaccurate, with citizens typically overestimating values. We observe an unexpected correlation between carbon footprint and energy content estimates. Portion size impacts perceptions, with estimations increasing with larger portion sizes. Weight information impacts perceptions, with estimations of carbon footprint being lower, and estimates of energy content being higher when weight information is present. Input method significantly affects observed values, estimates of carbon footprint and energy content estimates were lowest using the text box, followed by the slider tool, highest estimates were given using multiple choice. Citizens are unable to accurately estimate the carbon footprint and energy content of foods, though citizens may possess understanding of the hierarchy of values. These compelling findings highlight the need for consumer education, with a focus on carbon footprint, to precede interventions intended to move consumers toward more sustainable and healthy diets. We have demonstrated that citizen science can be used successfully to measure food carbon footprint and energy content perceptions, and the slider tool offers greater sensitivity of estimation and functionality than other input methods.